Revision of the Chinese species of the genus Grouvellinus Champion, 1923 (Coleoptera: Elmidae). The G. acutus species group - Bian, Dongju; Jäch, Manfred A. (Zootaxa, 2018)
The Grouvellinus acutus species group is established. In China, it includes three species, Grouvellinus acutus sp. nov. (Fujian, Guangxi), G. denticulatus sp. nov. (Yunnan), and G. fujianensis sp. nov. (Fujian, Guangxi), which are described herein. A possible case of hybridization is reported. Habitus photographs and detailed line drawings of the genitalia are provided.